2017
DOI: 10.1111/jfpp.13404
|View full text |Cite
|
Sign up to set email alerts
|

The effects of ozonated water on the microbial counts and the shelf life attributes of fresh-cut spinach

Abstract: Fresh-cut vegetables became more and more popular due to healthy eating habits, with main problem safety of the product because of microbial spoilage as well as visual and nutritional quality changes. Ozone may act as a sanitizer; however, due to its strong oxidant activity care is needed, as in some cases, that is, if the dose being used is too high, the quality of the produce may be reduced. In this study, ozonated water at various concentrations and dipping times (0, 0.4, 0.8, or Practical applicationsThe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 45 publications
2
15
0
Order By: Relevance
“…These results agreed with those of Papachristodoulou et al. (2018), who showed that aqueous ozone decreased Gram‐ and Enterobacteriaceae sp. loads on fresh‐cut melon during the first 5 days of storage.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…These results agreed with those of Papachristodoulou et al. (2018), who showed that aqueous ozone decreased Gram‐ and Enterobacteriaceae sp. loads on fresh‐cut melon during the first 5 days of storage.…”
Section: Resultssupporting
confidence: 93%
“…With an increase in storage time, the respiratory rates of all groups decreased gradually, and there was no significant difference between groups at the later stages of storage. The effect of aqueous ozone on the respiration rate of fresh‐cut products is controversial (Chauhan, Raju, Ravi, Singh, & Bawa, 2011; Papachristodoulou et al., 2018). It is possible that the effect of ozone water on the respiration rate depends on several factors, such as the type of vegetal tissue, product variety, dose, treatment time, and temperature (Silveira et al., 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The natural contamination of raw vegetables is normally high due to the close association with soil, and there is a high risk for contamination through irrigation water [26]. RTE vegetables, including leafy vegetables, are often contaminated with a large microbial population, typically in the range 5 to 7 log CFU/g [27,28]. Washing of fresh produce with tap water is frequently applied in an attempt to remove soil and microorganisms.…”
Section: The Rte Seafood Trend From a Food Safety Perspectivementioning
confidence: 99%
“…Ultrasound can be combined with other technologies such as ozone to enhance the efficiency at the industrial level, thereby reducing processing time. Ozone has been recognized as a "Generally Safe Substance" (GRAS) (Khadre, Yousef, & Kim, 2001;KIM, Yousef, & Chism, 1999) due to its capacity of effectively inactivating bacteria, viruses, fungi and mycotoxins without harmful residues (Coll Cardenas, Andres, Giannuzzi, & Zaritzky, 2011;Papachristodoulou, Koukounaras, Siomos, Liakou, & Gerasopoulos, 2018). Ozone processing has been found to be effective in extending the shelf-life of oranges, raspberries, grapes, pears and apples (Skog & Chu, 2001).…”
Section: Introductionmentioning
confidence: 99%